Effect of Eccentric Loading on Shear Load Capacity of Footings. - Mukisa, Fred (Kabale University, 2024)
Eccentric loading on footings is a common occurrence in structural design, yet its impact on shear load capacity remains poorly understood. This research aims to investigate the effect of eccentric loading on the shear load capacity of footings, exploring the relationships between eccentricity, shear stress distribution, footing dimensions, soil properties, and shear load capacity reduction. Through a combination of numerical modeling and analytical analysis, this study will develop a comprehensive understanding of the behavior of footings under eccentric loading. The research will culminate in the development of practical design guidelines, equations, and charts to predict the shear load capacity of footings under eccentric loading, validated by numerical data. The findings will contribute to improved design practices, enhanced structural safety, and reduced construction costs.